Atypical perspectives on project management: moving beyond the rational, to the political and the psychosocial. (2015) - Saint-Macary, Jan; Ika, Lavagnon A.
In the main, project management subscribes to an objective view of the organisation, relatively free of political and psychosocial tensions. But, this may be misleading in the context of projects where the stakes are numerous and complex. The article views the project from three perspectives: the conventional rational perspective, with the prism of the mandate; the atypical political perspective, with the prism of the principals; and the atypical psychosocial perspective, with the prism of the agents. It emerges that the rational perspective may be sufficient to assess and manage a project when efficiency prevails in both the parent and the client organisations. However, the project manager would be better served to use an integrative approach that also includes the political perspective when the organisations involved have differing expectations regarding the project, as well as the psychosocial perspective when project team members have a great deal of autonomy.